Gain-of-function factor H–related 5 protein impairs glomerular complement regulation resulting in kidney damage - Malik,TH; Gitterman,DP; Lavin,DP; Lomax-Browne,HJ; Hiemeyer,EC; Moran,LB; Boroviak,K; Cook,HT; Gilmore,AC; Mandwie,M; Ahmad,A; Alexander,IE; et al. (Proceedings of the National Academy of Sciences, 2021)
Genetic variation within the factor H–related (FHR) genes is associated with the complement-mediated kidney disease, C3 glomerulopathy (C3G). There is no definitive treatment for C3G, and a significant proportion of patients develop end-stage renal disease. The prototypical example is CFHR5 nephropathy, through which an internal duplication within a single CFHR5 gene generates a mutant FHR5 protein (FHR5mut) that leads to accumulation of complement C3 within glomeruli. To elucidate how abnormal FHR proteins cause C3G, we modeled CFHR5 nephropathy in mice. Animals lacking the murine factor H (FH) and FHR proteins, but coexpressing human FH and FHR5mut (hFH-FHR5mut), developed glomerular C3 deposition, whereas mice coexpressing human FH with the normal FHR5 protein (hFH-FHR5) did not. Like in patients, the FHR5mut had a dominant gain-of-function effect, and when administered in hFH-FHR5 mice, it triggered C3 deposition. Importantly, adeno-associated virus vector-delivered homodimeric mini-FH, a molecule with superior surface C3 binding compared to FH, reduced glomerular C3 deposition in the presence of the FHR5mut. Our data demonstrate that FHR5mut causes C3G by disrupting the homeostatic regulation of complement within the kidney and is directly pathogenic in C3G. These results support the use of FH-derived molecules with enhanced C3 binding for treating C3G associated with abnormal FHR proteins. They also suggest that targeting FHR5 represents a way to treat complement-mediated kidney injury.